Rethinking relationships in cyberspace. Issue 2 (1st September 2020) - Midson, Scott; O'Donnell, Karen
ABSTRACT: The ubiquity of the internet, which has been extensively theorised in the social sciences, provides, for some, a radically new context in which we must rethink both the significance and the performance of being human. For others, the internet is an extension rather than revision of our pre-existing practices, meaning that what it is to be human remains largely unchanged. This is a stimulating and pressing context for theological anthropological reflection: theological doctrines do not specifically address cyberspace, but they suggest idea(l)s of being human that are, on the one hand, enduring and yet can also be read as flexible for different contexts. What, then, are the challenges and promises that digital contexts pose for models of theological anthropology, specifically ones that highlight the significance of human relationships? Do digital contexts overstretch idea(l)s of human nature? On what grounds can we assess and reflect on our conduct in cyberspace?